The Dialectics of Middleness: Towards a Political Ontology of Centrism - Pendakis, Andrew (My University, 2010)
This dissertation explores the recent history and politics of the formation of the center or middle as the sovereign horizon of contemporary political practice and history. The political center has typically been imagined as the space between the two poles of Left and Right. Rather than beginning with an assumption of the political center's absolute relativity-a history absorbed by infinitely contingent contexts-this thesis understands centrism as itself a political position: a plural, yet relatively stable complex of meanings in urgent need of problematization. Guided methodologically by the work of Michel Foucault and Frederic Jameson, the thesis grounds this analysis in a reading of The Economist magazine between the years 1950-2007. A self-identified advocate of the "extreme center", the magazine functions as a primary archive through which to document shifts in the constitution of an historically-specific centrism, a political position with significant global traces and consequences.
In the Introduction the basic theoretical coordinates of the center as a metaphor, concept and political fantasy are unpacked against the backdrop of a broader diagnostics of the present. Chapter 1 addresses itself to the Keynesian centrism prevalent in the years immediately following the war in Britain, one characterized primarily by ideas about balance, consensus, and moderation. Chapter 2 follows the content of this discourse across the break-down of post-war growth and its subsequent identification with "radical" Thatcherism. In Chapter 3, the contradictions accumulated in this shift from a thematics of caution to one emphasizing a radical break with consensus, are examined through the figure of the heretical manager, the pragmatist who presides over the inherently revolutionary fabric of capitalist space and innovation. Finally, the conclusion thinks through the ways in which the radical center functions within a broader cultural sensation of middleness very much a basic part of life in postmodern societies.
Keywords: dialectics, middleness, political, ontology, centrism, global